Mapping Morphonosemantic Categories in Javanese Onomatopoeia - Fitriana, Ita; Suparno, Darsita (Linguistik Indonesia, 2025)
This study presents an in-depth analysis of the morphonosemantics process in Javanese onomatopoeia by applying the theoretical framework developed by Fitriana (2022) for Japanese mimetic language. Using a descriptive qualitative approach, data on onomatopoeia and its derivatives were collected from a corpus of contemporary Javanese magazines. This analysis, which focuses on the interaction between form and meaning, reveals that Javanese systematically utilizes phonological transformations and morphological processes to encode gradations of meaning. The main findings show that phonological alternations, particularly shifts in vowel quality (e.g., from front-high vowels to back-low vowels), consistently correlate with augmentative changes in size, mass, and strength. Meanwhile, morphological processes such as infixation (e.g., the insertion -um-), reduplication, and prenasalization systematically intensify the duration, repetition, or strength of an action or state. This detailed analysis of over 483 onomatopoeic forms contributes to the documentation of a threatened language variety and enriches the understanding of iconicity in minority languages. The study highlights the systematic relationship between phonological changes and semantic shifts in Javanese onomatopoeia, demonstrating its cultural and linguistic significance.